Swedish economic policy: Some current problems - F. E. Banks (Intereconomics, 1974)
During recent years sharp increases in unemployment have given rise to questions concerning the traditional way of managing the Swedish economy. Various aspects of the resulting discussion are reviewed in the following article.
Keywords: 330; Sweden